2021
DOI: 10.1186/s12891-021-04862-w
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps muscle strength recovery with the use of high tone power therapy after anterior cruciate ligament reconstruction: a randomized controlled trial

Abstract: Background There are no scientific reports clearly describing the effectiveness of the High Tone Power Therapy in patients after ACL reconstruction. This caused that in own research an attempt was made to present the possibilities of using the selected method of electrical stimulation in the treatment of an orthopaedic patient. The aim was to assess the effectiveness of electro stimulation of the quadriceps muscle in patients after ACL reconstruction, with the use of High Tone Power Therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Included studies assessed the effectiveness of Kinesio Taping (KT; three studies) [ 30 , 31 , 32 ], Whole body vibration (WHB; two studies) [ 33 , 34 ], Local Vibration Training (LVT; one study) [ 35 ], trigger point dry needling (TrPDN; one study) [ 36 ], High Tone Power Therapy (HiToP; one study) [ 37 ], alternating magnetic field (one study) [ 38 ], and app-based active muscle training program (App-Based Serious Gaming; one study) [ 39 ]. The included studies were conducted in Italy [ 32 , 34 ], France [ 31 , 35 ], Poland [ 37 , 38 ], Germany [ 33 , 39 ], Spain [ 36 ] and Turkey [ 30 ]. In this review, we included two articles published in 2021 by the same author.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Included studies assessed the effectiveness of Kinesio Taping (KT; three studies) [ 30 , 31 , 32 ], Whole body vibration (WHB; two studies) [ 33 , 34 ], Local Vibration Training (LVT; one study) [ 35 ], trigger point dry needling (TrPDN; one study) [ 36 ], High Tone Power Therapy (HiToP; one study) [ 37 ], alternating magnetic field (one study) [ 38 ], and app-based active muscle training program (App-Based Serious Gaming; one study) [ 39 ]. The included studies were conducted in Italy [ 32 , 34 ], France [ 31 , 35 ], Poland [ 37 , 38 ], Germany [ 33 , 39 ], Spain [ 36 ] and Turkey [ 30 ]. In this review, we included two articles published in 2021 by the same author.…”
Section: Resultsmentioning
confidence: 99%
“…In the included studies, we found a high level of heterogeneity regarding different interventions, outcomes, and measures but also imprecision of estimates, which did not allow us to undertake a detailed meta-analysis. Knee function was the most measured outcome in eight studies [ 30 , 32 , 33 , 34 , 35 , 36 , 37 , 39 ]; pain [ 30 , 31 , 32 , 36 , 37 , 39 ], ROM [ 30 , 32 , 33 , 36 , 37 , 38 ], and strength of extensor muscles [ 30 , 33 , 34 , 35 , 37 , 39 ] were evaluated in six studies; edema in five studies [ 30 , 32 , 37 , 38 , 39 ] and strength of flexor muscles in three studies [ 30 , 33 , 34 ]. A subgroup analysis with a synthesis of the outcomes is presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The modular teaching originates from the vocational education in European and American countries, and the competency-based education (CBE) mode and MES mode have become popular in China at present. The former focuses on the vocational ability training and the latter on the professional skill training [ 21 ]. Compared with the CBE mode, the MES mode adopted in this study more complies with the requirements of orthopedic rehabilitation in practice [ 22 – 24 ].…”
Section: Discussionmentioning
confidence: 99%